Disrupting Heteronormative Temporality through Queer Dramaturgies: Fun Home, Hadestown and A Strange Loop - Sarah K. Whitfield (Arts, 2020)
This article considers how André De Shields performance in Hadestown (2019), and the musicals Fun Home (2015) and A Strange Loop (2019) can be seen to respond to the present moment and argues that they disrupt heteronormative temporality through queer dramaturgy. It explores musicals that present queer performativity and/or queer dramaturgies, and addresses how they enact queer strategies of resistance through historical materialist critiques of personal biographies. It suggests that to do this, they disrupt the heteronormative dramaturgical time of the musical, and considers how they may enact structural change to the form of the musical. The article carries out a close reading of De Shields’ performance practice, and analyses the dramaturgy of Fun Home and A Strange Loop through drawing on the methodologies of José Muñoz and Elizabeth Freeman. It considers how they make queer labour visible by drawing on post-dramatic strategies, ultimately suggesting that to varying extents, these musicals offer resistance to the heteronormative musical form.